Strategies for Use Case Modeling: A Systematic Literature Review - Bispo, Cristiana Pereira; Magalhães, Ana Patrícia; Fernandes, Sergio (Companion Proceedings of the Brazilian Symposium on Software Engineering (SBES); 2019: Companion Proceedings of the 33th Brazilian Symposium on Software Engineering, 2020)
A major challenge in teaching use-case modeling (UCM) is to mitigate the difficulties of students that prevent them from producing use-case models with quality. The strategies for UCM are scattered in the literature in several areas, and may not be known to the students, who therefore fail to receive the benefits that would mitigate their difficulties. This paper aims to present a systematic literature review (SLR) to identify, gather and analyze strategies for UCM. During the SLR, two thousand two hundred sixty-six studies published between 2008 and 2018 were returned from 6 bases (ACM, IEEE, Scopus, Science Direct, SpringerLink and Engineering Village), which resulted in the selection of 39 primary studies. These were classified, following the coding procedures of Grounded Theory, into 13 categories of different strategies for UCM. The results can help teachers in the adoption of the most appropriate UCM strategies for their students. Besides, they provide a quick reference for teachers and researchers interested in conducting additional studies on teaching strategies for UCM.